SINTESIS MAGNETIT-Mg/Al HIDROTALSIT DAN APLIKASINYA UNTUK ADSORPSI ZAT WARNA NAVY BLUE DAN YELLOW F3G - , Lutfia Isna Ardhayanti ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Synthesis of Magnetite-Mg/Al Hydrotalcite (M-Mg/Al HT) and its application for Navy Blue (NB) and Yellow F3G (YF3G) dyes adsorption has been studied. Magnetite was synthesized by co-precipitation from a mixed solution containing FeCl3.6H2O and FeSO4.7H2O with molar ratio of Fe(III) and Fe(II) 2:1. Mg/Al HT was produced through co-precipitation from a mixed solution containing Mg(NO3)2.6H2O and Al(NO3)3.9H2O with molar ratio of Mg(II) and Al(III) 2:1. The same as Mg/Al HT, M-Mg/Al HT was also synthesized through co-precipitation, but magnetite was first dispersed in the mixed solution of Mg(II) and Al(III). M-Mg/Al HT was used as adsorbent in adsorption of NB and YF3G dyes to determine the optimum conditions which included medium acidity, interaction time and concentrations of NB and YF3G. The obtained optimum condition was then used as condition for adsorption of the mixture of NB and YF3G dyes by M-Mg/Al HT. In addition to M-Mg/Al HT, Mg/Al HT was used also as adsorbent for comparison. After being used as adsorbent, M-Mg/Al HT and Mg/Al HT were calcined and then utilized again to adsorp dyes in order to evaluate their effectiveness to be reused. The results showed M-Mg/Al HT was successfully synthesized using coprecipitation method as confirmed by its XRD diffractogram showing the presence of characteristic peaks for magnetite and Mg/Al HT. The optimum condition of adsorption for the two dyes by M-Mg/Al HT was at pH 4 with interaction time 60 minutes. The adsorption kinetics followed the pseudo-second-order kinetic model with rate constant of 9710 g/(mol.min) for NB and 18367 g/(mol.min) for YF3G. Adsorption data followed the Langmuir isotherm model with adsorption capacity was 0.546 x 10-3 mol/g for NB and 0.392 x 10-3 mol/g for YF3G. M-Mg/Al HT had a much higher adsorption capacity for the mixture of NB and YF3G, i.e. 63.75 mg/g, compared to Mg/Al HT, i.e. 15.67 mg/g. After being used and calcined, the adsorbents showed higher adsorption capacities, i.e. 81.67 mg/g for M-Mg/Al HT and 81.58 mg/g for Mg/Al HT.